Numerical Simulation of Wake-Field Acceleration Using an Eulerian Vlasov Code (Communications in Computational Physics, 2008)
We study the generation of nonlinear plasma wake fields by intense laser pulses, using an Eulerian code for the numerical solution of the fully relativistic one-dimensional (1D) Vlasov-Maxwell equations. The examination of the phase-space of the distribution function allows to study without numerical noise aspects of the particle acceleration by the wake-field generated by intense laser pulses, in the very low density regions of the phase-space. We study the effect of the thermal spread on the existence of accelerated beams, and we compare between results obtained from a circularly polarized wave and a linearly polarized wave.